A Tri Kaya Parisudha-Based Character Education Internalization Model For Strengthening The Character Of Second-Semester Students - I Komang Badra; I Made Sujana Adnyana (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
The decline of moral values and character among young generations in the digital era has become a significant challenge for higher education institutions, including Hindu-based colleges. Character education is therefore essential to develop students who possess ethical awareness, responsibility, and positive behavior. This study aims to develop a Tri Kaya Parisudha-based Character Education Internalization Model for strengthening the character of second-semester students. Tri Kaya Parisudha, a fundamental Hindu ethical concept encompassing purity of thought (manacika), speech (wacika), and action (kayika), serves as the philosophical foundation of the model. This research employed a Research and Development (R&D) approach using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The participants were second-semester students at STKIP Agama Hindu Amlapura. Data were collected through observations, interviews, questionnaires, and documentation. The validity of the model was assessed by experts in character education, Hindu religious education, and instructional design, while practicality and effectiveness were evaluated through field implementation. The findings indicate that the developed model is valid, practical, and effective in strengthening students’ character. The implementation of the model contributed to improvements in ethical awareness, self-discipline, responsibility, honesty, respect, and social behavior. Furthermore, the integration of Tri Kaya Parisudha values into learning activities encouraged students to internalize positive attitudes through reflective thinking, ethical communication, and constructive actions. The study concludes that the Tri Kaya Parisudha-based character education internalization model can serve as an innovative pedagogical framework for character development in higher education, particularly within Hindu educational institutions.